Forced axisymmetric vibrations of a thick circular rigidly fixed piezoceramic plate - Shlyakhin, D. A. (Mechanics of solids, 2014)
A new closed-form solution of the axisymmetric nonstationary problem of elasticity is constructed for a circular thick piezoceramic plate whose outer cylindrical surface is rigidly fixed. The use of mixed boundary conditions for a curvilinear plane allows one to obtain sufficiently simple computational relations. The closed-form solution is constructed by the method of expansion in the vector eigenfunctions in the form of a structure algorithm of finite transformations. The obtained solutions are used to determine the natural vibration frequency, the stress-strain state of the considered element, and all characteristics of the induced electric field.